Preparation, characterization and phenol adsorption capacity of activated carbons from African beech wood sawdust - N.T. Abdel-Ghani; G.A. El-Chaghaby; F. Helal (Global Journal of Environmental Science and Management)
In the present study, different activated carbons were prepared from carbonized African beech wood sawdust by potassium hydroxide activation. The activated carbons were characterized by brunauer–emmett–teller, scanning electron microscope, fourier transform infrared spectroscopy, and thermogravimetric analyzer. The phenol adsorption capacity of the prepared carbons was evaluated. The different factors affecting phenol’s removal were studied including: contact time, solution pH and initial phenol concentration. The optimum phenol removal was obtained after a contact time of 300 min. and at an initial phenol solution pH 7. The maximum removal percentages were determined at 5mg/l initial phenol concentration as 79, 93, 94 and 98% for AC0, AC1, AC2 and AC3; respectively. The adsorption of phenol on African beech sawdust activated carbons was found to follow the Lagergren first order kinetics and the intraparticle diffusion mechanism gave a good fit to the experimental data. The isothermal models applied fitted the experimental data in the order: Langmuir> Dubinin–Radushkevich> Freundlich and Temkin.